Effectiveness of translation transformations in different styles of the english language for teaching written translation - Cherchata, Lidiia; Korol, Larysa; Rubchak, Olha; Orda, Oleksandra; Novytska, Dariia (My University, 2023)
The issue of translation transformations for teaching written translation has been studied rarely. This study has the general purpose of urging the importance of the issue, especially in view of global digitalization, when machine translation poses a threat to flatten out the role of a human translator. A translator who does not have translation transformations skills is not in demand on the labour market. The aim of the article is to determine the effectiveness of using the method of translation transformations as a special educational technology. The method of translation transformations is tested through its application for training future foreign philologists in the written translation techniques of English texts of different styles. The final evaluation showed that on average, the respondents of the experimental group achieved the level of “Very good” (827.4 points, qualitative level – 82.8%), and the respondents of the control group – the level of “Good” (754.6 points, qualitative level – 75.5%). The data indicate the effectiveness of the method of translational transformations. However, they evidence the difficulty of achieving more significant results within the scope of a time-limited experiment.

Перекладацькі трансформації для навчання письмового перекладу є темою, яка рідко стає предметом уваги. Представлена розвідка має загальну ціль актуалізувати тему. Надто на тлі глобальної діджиталізації, коли машинний переклад загрожує нівелювати роль перекладача-людини. Перекладач без навичок перекладацьких трансформацій в умовах сьогодення не є затребуваним на ринку праці. Мета статті - визначити ефективність застосування методу перекладацьких трансформацій як спеціальної навчальної технології. Метод перекладацьких трансформацій випробувано на прикладі його застосування для навчання майбутніх іноземних філологів техніки письмового перекладу текстів різних стилів (англійською мовою). Фінальне оцінювання показало, що респонденти експериментальної групи усереднено досягли рівня «Дуже добре» (827,4 бала, якісний рівень - 82,8%), а контрольної – рівня «Добре» (754,6 бала, якісний рівень перекладацьких трансформацій. Проте свідчать про складність досягти суттєвіших результатів за умов обмеженого в часі експерименту.
Ефективність перекладацьких трансформацій у різних стилях англійської мови для навчання письмового перекладу
Keywords: adaptation of the translated text; foreign philologists; translation accuracy; translation reliability; translation transformations; перекладацькі трансформації; адаптація перекладеного тексту; точність перекладу; достовірність перекладу; іноземні філологи